Watchdog or loyal servant? Political media bias in US newscasts - Lea Bernhardt; Ralf Dewenter; Tobias Thomas (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2020)
We investigate if four leading, electronic news gathering organizations in the US - ABC News, CBS News, FOX News, and NBC News - fulfill their role as the fourth estate in the US democracy. Our analysis, using the Political Coverage Index (PCI) introduced by Dewenter et al (2020), is based on the tonality of their political coverage using 815,000 human-coded news items from 2001 through 2012. For our econometric analysis, we use panel regressions with media and time fixed effects. To account for endogeneity, we cut time spans around national elections out of our data. In the remaining data, elections can be seen as a purely exogenous event. Focusing on the entire media set, we find robust empirical results for an anti-government bias in media reporting: Under Republican presidents, political coverage tends to be more liberal, whereas it tends to be more conservative if the president is a Democrat. However, when focusing on each single news organization, interesting differences emerge: For CBS News and NBC News, we find robust empirical evidence of anti-government-bias. In contrast, FOX News is always much more critical of Democrats than of Republicans. Hence, FOX News can be seen as a more loyal servant to one party rather than acting as the fourth estate. In addition, we find no evidence that ABC News significantly changes its position depending on the presidency. Although descriptive statistics show a certain tendency toward government-critical reporting by ABC News, the variation is not statistically significant.
Keywords: C43; D72; L82; 330; Political Coverage Index; government bias; tonality; media capture; US newscasts